Performer training reconfigured post-psychophysical perspectives for the twenty-first century - Camilleri, Frank (Methuen/Drama, 2019)
Offering a radical re-evaluation of current approaches to performer training, this is a text that equips readers with a set of new ways of thinking about and ultimately 'doing' training. Stemming from his extensive practice and incorporating a review of prevailing methods and theories, Frank Camilleri focuses on how material circumstances shape and affect processes of training, devising, rehearsing and performing. Frank Camilleri puts forward the 'post-psychophysical' as a more extended form of psychophysical discussion and practice that emerged and dominated in the 20th century. The 'post-psychophysical' updates the concept of an integrated bodymind in various ways, such as the notion of a performer's bodyworld that incorporates technology and the material world. Offering invaluable introductions to a wide range of theories around which the book is structured - including postphenomenological, sociomaterial, affect and situated cognition - this volume provides readers with an enticing array of critical approaches to training and creative processes"--